Keadilan Substantif Dalam Kriminalisasi Tindak Pidana Lingkungan Hidup: Analisis Terhadap Kuhp Dan Uu Pplh - surya, maya; Budi Sastra Panjaitan; Arifuddin Muda Harahap (widya balina, 2025)
Abstract. The environment is not merely a legal object, but rather a living space for humans that is intertwined with the continuity of life itself. In this context, the criminalization of environmental crimes must be understood as an effort to uphold substantive justice, not merely the fulfillment of legal procedures. This article examines the comparison between the 2023 Criminal Code and Law No. 32 of 2009 (Environmental Protection and Management Law), as well as the alignment of both in responding to ecological crimes. With a normative juridical approach and philosophical analysis, a tension was found between the formalistic approach in the Criminal Code and the ecological approach in the Environmental Protection and Management Law. This inconsistency has the potential to obscure the substance of environmental justice. Therefore, a renewal of the penal paradigm that favors the intrinsic value of nature and the principle of sustainability is necessary. Abstrak. Lingkungan hidup bukan sekadar objek hukum, melainkan ruang hidup manusia yang menyatu dengan keberlangsungan kehidupan itu sendiri. Dalam konteks ini, kriminalisasi tindak pidana lingkungan harus dimaknai sebagai upaya menegakkan keadilan substantif, bukan semata pemenuhan prosedur hukum. Artikel ini mengkaji perbandingan antara KUHP 2023 dan UU No. 32 Tahun 2009 (UU PPLH), serta menelaah keselarasan keduanya dalam merespons kejahatan ekologis. Dengan pendekatan yuridis normatif dan analisis filosofis, ditemukan adanya ketegangan antara pendekatan formalistik dalam KUHP dan pendekatan ekologis dalam UU PPLH. Ketidaksinambungan ini berpotensi mengaburkan substansi keadilan lingkungan. Oleh karena itu, diperlukan pembaruan paradigma pemidanaan yang berpihak pada nilai intrinsik alam dan prinsip keberlanjutan.